Multiselfing in Music Education - Radio Cremata (Education Sciences)
Multiselfing is a form of musicianship where one person digitally clones themself into several single selves, creating layers and a musical collective that would otherwise be impossible without the mediation of technology. There are various kinds of multiselfers. This article categorizes them as the following: singers, instrumentalists, loopers, live performers, and hybrids. While these five categories are presented distinctly here, they may often overlap. This article explores the notion of multiselfing and its implicit potential when situated in music education to develop comprehensive music skills. Comprehensive musicianship is important because it enables students to grow in broad musical knowledge and skills at all levels of instruction by synthesizing the musical materials they are working with and by making conceptual connections through performance, analysis, and composition. In addition to including many examples, this article also includes lists of resources and applications to help schoolteachers better understand how to integrate multiselfing into their pedagogic practices.